Comparison of diagnostic and treatment guidelines for undescended testis - Jaeho Shin; Ga Won Jeon (The Korean Pediatric Society, 2020)
Cryptorchidism or undescended testis is the single most common genitourinary disease in male neonates. In most cases, the testes will descend spontaneously by 3 months of age. If the testes do not descend by 6 months of age, the probability of spontaneous descent thereafter is low. About 1%-2% of boys older than 6 months have undescended testes after their early postnatal descent. In some cases, a testis vanishes in the abdomen or reascends after birth which was present in the scrotum at birth. An inguinal undescended testis is sometimes mistaken for an inguinal hernia. A surgical specialist referral is recommended if descent does not occur by 6 months, undescended testis is newly diagnosed after 6 months of age, or testicular torsion is suspected. International guidelines do not recommend ultrasonography or other diagnostic imaging because they cannot add diagnostic accuracy or change treatment. Routine hormonal therapy is not recommended for undescended testis due to a lack of evidence. Orchiopexy is recommended between 6 and 18 months at the latest to protect the fertility potential and decrease the risk of malignant changes. Patients with unilateral undescended testis have an infertility rate of up to 10%. This rate is even higher in patients with bilateral undescended testes, with intra-abdominal undescended testis, or who underwent delayed orchiopexy. Patients with undescended testis have a threefold increased risk of testicular cancer later in life compared to the general population. Self-examination after puberty is recommended to facilitate early cancer detection. A timely referral to a surgical specialist and timely surgical correction are the most important factors for decreasing infertility and testicular cancer rates.